Hope Azevedo: capstone - Azevedo, Hope, artist (Colorado State University. Libraries, 2025)
The artist's statement: My name is Hope Azevedo. I've always believed one of the most powerful ways to receive messages is through vision. Our memories are often associated with what we see. As result, I've decided to turn the changes I wish to see in the world into designs. Even the simplest of advertisements deserves to be created with care and devotion. Graphic Design inspires me wherever I go. Our daily lives are filled with design without us even realizing it, and as a designer, it's important that these experiences are enjoyable. The world is rapidly changing with AI slowly taking over this medium, and it is important that we don't allow the human touch to fade from design. Because of this, I am inspired to keep the human touch within design. To me, people provide such passion and individuality to design. Collaborating and watching designs become one amongst artists is something that artificial intelligence can never replicate. Professionally, I like to adhere to my personal style while ensuring each piece is up to standard. I don't see my projects as complete until my team and I are satisfied with the visual result. All this to say, we mustn't take the human connection of design for granted. People are so vital in the processes of design, especially when trying to convey a message. My intention is to keep this artistic touch of humanity alive with passion in every design I create.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design